2021
DOI: 10.1177/15347354211051622
|View full text |Cite|
|
Sign up to set email alerts
|

Awareness, Use and Outlook of Complementary and Alternative Medicine (CAM) Options in an Underserved, Uninsured Minority Cancer Patient Population

Abstract: Integrative oncology aims to coordinate the delivery of conventional medicine and evidence-supported complementary and alternative medicine (CAM) to patients receiving cancer care. This field developed out of an increased interest in CAM usage among cancer patients. However, CAM use among medically underserved cancer patients remains to be well characterized. We evaluated CAM awareness as well as prevalence and characteristics of CAM use in 170 consecutive, medically underserved cancer patients presenting to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“… 26 Bari et al’s cross-sectional survey-based study included a sample of 100 survivors of any type of cancer (the majority of participants had lung cancer) who identified as coming from an uninsured, minority background; 98% of this study sample identified as African American. 11 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“… 26 Bari et al’s cross-sectional survey-based study included a sample of 100 survivors of any type of cancer (the majority of participants had lung cancer) who identified as coming from an uninsured, minority background; 98% of this study sample identified as African American. 11 …”
Section: Resultsmentioning
confidence: 99%
“…Four of the qualitative studies followed a focus group design, 8 , 18 , 24 , 25 one was a qualitative descriptive study, 26 and one was a cross-sectional survey-based study. 11 Yan et al’s study conducted 8 focus groups with 40 AACS (breast cancer) using a social-cognitive model to ask participants about their experiences with breast cancer survivorship and recommend culturally sensitive interventions for future survivors. 24 Smith et al’s 25 intervention focused on intervention recommendations through 4 focus groups of 60 AACS (breast cancer), and participants answered questions about barriers to socio-ecological physical activity.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations